1982
DOI: 10.1007/bf02541016
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the chemical structures of natural antioxidants isolated from rosemary

Abstract: A natural antioxidant extract with activity greater than BHA and equal to BHT was isolated from rosemary leaves. The extract was separated into 7 primary fractions with liquid chromatography, using silicic acid as an adsorbent followed by gradient elution. Each fraction was rechromatographed to yield a total of 16 subfractions. Two compounds, carnosol and ursolic acid, were identified by infrared, mass and nuclear magnetic resonance spectrometry. Carnosol was shown to be one of the active antioxidant component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
10

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(87 citation statements)
references
References 6 publications
3
74
0
10
Order By: Relevance
“…The leaves of Rosmarinus offi cinalis (Lamiaceae) were collected from cultivated plants in Zacatecas, México, and were authenticated by Jesús Balleza Cadengo at the Botanical Department of the Unidad Académica de Agronomía, Universidad Autónoma de Zacatecas, México. Leaves were shadedried and the plant extract was obtained by a modifi cation to the method reported by Wu et al (1982). Briefl y, 1 kg of dried leaves were powdered and extracted with 6 L methanol at 60 °C for 2 h. After extraction, the mixture was fi ltered and the fi ltrate treated three times with 200 g activated charcoal then fi ltered to yield a light-brown fi ltrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves of Rosmarinus offi cinalis (Lamiaceae) were collected from cultivated plants in Zacatecas, México, and were authenticated by Jesús Balleza Cadengo at the Botanical Department of the Unidad Académica de Agronomía, Universidad Autónoma de Zacatecas, México. Leaves were shadedried and the plant extract was obtained by a modifi cation to the method reported by Wu et al (1982). Briefl y, 1 kg of dried leaves were powdered and extracted with 6 L methanol at 60 °C for 2 h. After extraction, the mixture was fi ltered and the fi ltrate treated three times with 200 g activated charcoal then fi ltered to yield a light-brown fi ltrate.…”
Section: Methodsmentioning
confidence: 99%
“…Its antioxidant activity is well documented (Wu et al, 1982) and the activity has been ascribed to both the diterpene content, mainly carnosic acid and carnosol (Wijeratne and Cuppett, 2007), as well as to the essential oil constituents (Bozin et al, 2007). Several methods have now been developed to obtain suitable extracts of Rosmarinus offi cinalis with high antioxidant activity (Cuvelier et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary leaves .were collected from the garden of the Mediterranean Agronomic Institute of Chania (MAICh) and the rosemary methanol extracts were prepared according to the method proposed by Wu et al, (1982). The vegetable water was obtained 422 Grasas y Aceites from the Institute of Subtropical and Olive Trees of Chania.…”
Section: Preparation Of Rosenriary and Vegetable Water Additives (Extmentioning
confidence: 99%
“…(Wu et al, 1982;Inatani et al, 1983;Houlihan étal., 1985;Chen étal., 1992). The results indicated that rosemary extract obtained by different polarities solvents an antioxidant activity on olive and sesame oils at 55 °C.…”
Section: Resultsmentioning
confidence: 99%